2014
DOI: 10.1038/cddis.2014.367
|View full text |Cite
|
Sign up to set email alerts
|

The DNA methylation-regulated miR-193a-3p dictates the multi-chemoresistance of bladder cancer via repression of SRSF2/PLAU/HIC2 expression

Abstract: Chemoresistance hinders the curative cancer chemotherapy. To define the role of the DNA methylation-regulated microRNA (miR) genes in the chemoresistance of bladder cancer, we performed both DNA methylomic and miRomic analyses of a multi-chemosensitive (5637) versus a multi-chemoresistant (H-bc) cell line and found that miR-193a-3p is hypermethylated/silenced in 5637 and hypomethylated/expressed in H-bc cells. A forced reversal of its level turned around the chemoresistance in the cultured cells and the tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
118
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(124 citation statements)
references
References 52 publications
4
118
0
Order By: Relevance
“…It has been demonstrated that miRNAs are involved in regulating over 30 % of all human genes [5]. Thus, a single miRNA can control more than 100 genes' expression, which handles many cellular processes including cell proliferation, apoptosis, metastasis, and chemoresistance [6][7][8]. The dysregulated miRNA expression has been found in various cancers [9,10], which indicates that miRNAs are implicated in the tumor development and progression.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that miRNAs are involved in regulating over 30 % of all human genes [5]. Thus, a single miRNA can control more than 100 genes' expression, which handles many cellular processes including cell proliferation, apoptosis, metastasis, and chemoresistance [6][7][8]. The dysregulated miRNA expression has been found in various cancers [9,10], which indicates that miRNAs are implicated in the tumor development and progression.…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs regulate the expression of a variety of target genes and their dysregulation is closely related to the development of diseases including cancer. The abnormal expression of miRNAs in cancer contributes to almost every field of tumor pathology [2, 3], including drug resistance [4], which remains a major obstacle to effective therapy of patients [5]. The multi-chemoresistance property differs dramatically among the cancer patients, even in the different cancer lesions of a single patient [6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, changes in alternative splicing of apoptotic genes influence sensitivity of cancer cells to chemotherapeutics, e.g., cisplatin or paclitaxel [44,45]. Interestingly, it was shown that SRSF2 contributes to chemoresistance in cancers of liver, bladder, and lung [46,47]. These observations suggest that SRSF2-mediated changes in apoptotic pathways may possibly contribute to resistance of renal cancer to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%